SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDI KASUS : DI SMP NEGERI 38 MEDAN) - Adil Setiawan (JSIK (Jurnal Sistem Informasi Kaputama), 2020)
The world of education taken so far is general, providing services in accordance with the rules that apply to all students, so it is very difficult to see the differences that exist between students in their interests, and talents. Therefore, it is very necessary to develop the advantages possessed by each student so that their interests and talents can become achievements. In order to motivate students to continue to excel and hone their talents, SMP Negeri 38 Medan conducts activities to be able to see the potential of students through the selection of high achieving students. A decision support system (SPK) can make it easier to choose high-achieving students and use Simple Additive Weighting (SAW) as a decision method. The Simple Additive Weighting (SAW) method is also known as the addition method. The basic concept in the SAW method is to find the number of performance ratings for each alternative that exists on all attributes. The Simple Additive Weighting (SAW) method requires the decision matrix normalization process (X) to a scale that can be compared with all available alternative ratings. The criterion that becomes an assessment in selecting high achieving students in SMP Negeri 38 Medan is to look at the average value of report cards, ranking, absenteeism, activeness in organizing, participating in competitions, discipline, and morality.